2022
DOI: 10.47278/journal.ijvs/2021.106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chilling Regimes on the Nutritional Value of Turkey Meat

Abstract: This paper studies changes in the mass fraction of moisture the content of proteins and fats in turkey meat, depending on the thermal state. The research materials were the chilled parts of turkey carcasses. There had established that defrosted meat contains less protein by 0.5%, fat 0.2%, and moisture 0.8% than chilled turkey meat. The difference between the re-defrosted meat and chilled meat by protein content is 1.4%, fat content is 0.6%, and moisture is 2.9%. This result indicates a significant decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[1,2]. In developing countries, a signifcant number of people are facing major nutritional problems including vitamin A defciency (VAD), iodine defciency (ID), iron defciency anemia (IDA), and protein energy malnutrition (PEM) due to inadequate intake of the daily recommended nutritional requirements that can be fulflled by consuming traditional foods such as fruits and vegetables [3][4][5][6][7]. Numerous studies have explored the potential of green leafy vegetables to address these nutritional problems as they are rich in nutrients and can be consumed daily.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2]. In developing countries, a signifcant number of people are facing major nutritional problems including vitamin A defciency (VAD), iodine defciency (ID), iron defciency anemia (IDA), and protein energy malnutrition (PEM) due to inadequate intake of the daily recommended nutritional requirements that can be fulflled by consuming traditional foods such as fruits and vegetables [3][4][5][6][7]. Numerous studies have explored the potential of green leafy vegetables to address these nutritional problems as they are rich in nutrients and can be consumed daily.…”
Section: Introductionmentioning
confidence: 99%
“…The primary disadvantage, however, associated with the higher proportion of the fines in the feed is reduced gizzard development (Abdollahi et al, 2013). It has been reported that the reduced gizzard development enhanced the passage of undigested nutrients from fore to hind gut, which in turn, negatively affects the feed efficiency (Wiernusz et al, 1995;Drozd et al, 2022). In addition, the undigested proteins that reach in hind gut are fermented by microbes and are responsible for synthesis of various compounds of secondary nature such as ammonia, indoles, phenols and amines, which further exert negative impacts on production traits and intestinal histomorphology in the broilers (Qaisrani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%